Serum albumin cysteine trioxidation is a potential oxidative stress biomarker of type 2 diabetes mellitus - Paramasivan, Selvam (2021)
Metabolic disorders in T2DM generate multiple sources of free radicals and oxidative stress that accelerate nonenzymatic degenerative protein modifications (DPMs) such as protein oxidation, disrupt redox signaling and physiological function, and remain a major risk factor for clinical diabetic vascular complications. In order to identify potential oxidative biomarkers in the blood plasma of patients with T2DM, we used LC-MS/MS-based proteomics to profile plasma samples from patients with T2DM and healthy controls. The results showed that human serum albumin (HSA) is damaged by irreversible cysteine trioxidation, which can be a potential oxidative stress biomarker for the early diagnosis of T2DM. The quantitative detection of site-specific thiol trioxidation is technically challenging; thus, we developed a sensitive and selective LC-MS/MS workflow that has been used to discover and quantify three unique thiol-trioxidized HSA peptides, ALVLIAFAQYLQQC(SO3H)PFEDHVK (m/z 1241.13), YIC(SO3H)ENQDSISSK (m/z 717.80) and RPC(SO3H)FSALEVDETYVPK (m/z 951.45), in 16 individual samples of healthy controls (n = 8) and individuals with diabetes (n = 8). Targeted quantitative analysis using multiple reaction monitoring mass spectrometry revealed impairment of the peptides with m/z 1241.13, m/z 717.80 and m/z 951.45, with significance (P < 0.02, P < 0.002 and P < 0.03), in individuals with diabetes. The results demonstrated that a set of three HSA thiol-trioxidized peptides, which are irreversibly oxidatively damaged in HSA in the plasma of patients with T2DM, can be important indicators and potential biomarkers of oxidative stress in T2DM.